Keputihan pada wanita - Gusti Ayu Marhaeni (Poltekkes Kemenkes Denpasar, 2017)
Abstract. Leucorrhea is a condition that is often suffering by women throughout the life cycle starting from adolescence, the reproductive period or menopause. Leucorrhea divided into two types: normal vaginal discharge or physiological and pathological abnormal. Abnormal vaginal discharge or a physiologically occurs in accordance with the female reproductive cycle or in accordance with the cycle of a woman's body with this type of expenditure is actually clear, odorless not excessive and does not cause itching or burning. While the pathological or abnormal vaginal discharge is characterized by the amount of release that much, such as sour milk, yellow or greenish, itching, burning, with a fishy smell or bad odor. The color of the vagina will be different according to the cause of vaginal discharge. The most common cause of abnormal vaginal leucore is: bacteria, fungi and parasites. Prevention of vaginal leucore the most important thing to do is maintain the cleanliness of the reproductive organs in the right way, a balance between activity and rest, reduce the of vaginal discharge are bacteria, fungi and parasite and also maintaining psycologycal stress. The purpose of this paper to discover the causes of vaginal leucorrhea. Method used was to search literature related leucorrhea. The search results show the causes are bacteria, fungi and paracites. Keywords: leucorrhea, vaginal discharge, woman